INDONESIA'S CONVENTIONAL ECONOMIC STABILITY AMIDST GLOBAL ECONOMIC UNCERTAINTY - Jojo Jojo; Ana Frasipa; Indri Pramesti S; Sulastri Sulastri (Sekolah Tinggi Ilmu Ekonomi Sutaatmadja, 2026)
This paper examines the resilience of Indonesia’s conventional economy amid heightened uncertainty in global markets. Over the last ten years, worldwide economic conditions have become increasingly unstable due to geopolitical tensions, disruptions in supply chains, volatility in commodity prices, and adjustments to monetary policies in developed nations. Adopting a qualitative, descriptive–exploratory method, the study investigates how Indonesia’s fiscal, monetary, and structural strategies interact to preserve macroeconomic balance under external shocks. The analysis relies on secondary data gathered from institutions such as Bank Indonesia, the Central Bureau of Statistics (BPS), the International Monetary Fund (IMF), and the World Bank covering the 2015–2025 period. Results indicate that Indonesia has maintained robust macroeconomic fundamentals, characterized by consistent growth, manageable inflation, and sufficient foreign reserves despite global disturbances. Domestic demand diversification and a resilient financial system have also supported this stability. Nonetheless, exposure to global interest rate shifts, commodity price swings, and capital flow volatility remains a challenge. Strengthened coordination between fiscal and monetary authorities, supported by structural reforms in industrial downstreaming and digital economic development, is vital to reinforce long-term resilience. The research concludes that credible and flexible macroeconomic policy synergy plays a crucial role in sustaining Indonesia’s stability in an era of global uncertainty.